Influence of CAR T-cell therapy associated complications - Umair, Mohammad Mussab; Lai, Xun; Xue, YuanBo; Yao, Hong (Frontiers in Oncology, 2025)
Since the introduction of chimeric antigen receptor (CAR) T-cell therapy, it has elicited an immense response in both targeted and residual cancers. Its clinical efficacy is often accompanied by a group of side effects that may become serious because of factors such as tumor burden, the extent of lymphodepletion, and the type of co-stimulus. It is also crucial to know the common toxicities associated with CAR T-cell therapy, including cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), cardiotoxicity, metabolic disorders, pulmonary toxicity, macrophage activation syndrome (MAS), prolonged cytopenia, coagulation disorders, and potential off-target effects on various organs. If not well managed, these can be fatal. However, knowledge about molecular pathways, calcineurin inhibitors, IL-6 receptor antagonists, steroids, suppression of nitric oxide synthase, various therapeutic approaches, and other recent advances have been developed to mitigate the fatal results of various short-term and chronic adverse events related to CAR T-cell therapy. This study provides a comprehensive perspective on contemporary management strategies and presumed causative processes of CAR T-cell-related adverse effects, albeit with several limitations. When CAR T-cell complications, costs, and challenges of toxicity management are properly considered, the CAR T-cell therapy of the future will include a number of toxicity-escaping options.